Welfare-Based Income Among Immigrants in the Netherlands: Differences in Social and Human Capital. Issue 2 (3rd April 2019) - Renema, Jeanette A. J.; Lubbers, Marcel
ABSTRACT: This study contributes to the structural migrants' integration literature with its focus on a wider understanding of welfare-based incomes among immigrants in the Netherlands. We examined whether immigrants' reliance on either unemploy-ment benefits, occupational disabilities benefits, or social assistance could be explained through human-capital and social-capital determinants. We found that this foremostly applies to social assistance–based incomes, presenting the relevance of disentangling various welfare schemes. We additionally proposed that more capital increases immigrants' knowledge about the welfare schemes' bureaucratic procedures and that under the condition of lacking employment more capital leads to higher chances for a welfare-based income, but we found little support for this explanation.